Torsional vibration dynamics of a gear-shafting system attaching a nonlinear energy sink. (15th August 2022) - Cao, Yanbo; Yao, Hongliang; Li, Hui; Dou, Jinxin
Highlights: Torsional vibration of a gear-shafting system is suppressed by a NES. NES is not installed on the excitation rotor. NES cannot change frequency compositions of meshing gear pairs. Vibration amplitudes of meshing frequencies are mitigated. The vibration inhibition ability of NES is verified by a test. Abstract: Torsional vibration of a gear-shafting system attaching a nonlinear energy sink (NES) is examined herein. Firstly, a gear-shafting system with two shafts is introduced and then dynamic model of the gear-shafting-NES system is established. Next, numerical simulations of gear-shafting-NES system on both the transient vibration and steady-state vibration are carried out. In the next part, the experimental verification of NES on the steady-state vibration suppression of the gear-shafting system is given. Incidentally, influences of the NES on the meshing frequency of gear pair are also studied. The results show that the steady-state vibration suppression rate of NES can reach 76.4% in simulation and 81.7% in test, and also the NES can inhibit the torsional vibration of the gear-shafting system even when it is not on the shaft of excitation source.